Data on the administrative workload and perceived administrative burden of farmers in SwitzerlandZenodo - Gabriele Mack; Christian Ritzel; Jeanine Ammann; Katja Heitkämper; Nadja El Benni (Data in Brief)
We present data from a paper-and-pencil survey of Swiss farmers. The survey was mailed to 2000 randomly selected Swiss farmers from the two largest Swiss language regions (German and French) in February 2019. A reminder was sent in April 2019. The response rate was around 40 % (N = 811). In the main part of the survey, we collected quantitative data on farmers’ workload and perceived burden due to (1) overall farming activities, (2) administrative activities related to the application of direct payments, and (3) other office work related to farm planning, bookkeeping, purchasing, and sales. We also asked farmers to rate their current workload and perceived administrative burden compared to five years earlier. We also collected data on the perceived burden of using e-government services, the administrative workload of various voluntary direct payment schemes, and the workload of inspections and sanctions. We collected personal information about the farmers. Finally, the farmers were asked to rate a series of statements regarding agricultural policy measures, the importance of inspection measures, the obligation to provide proof of eligibility for direct payments, information on current policy measures, and the justification of penalties for non-compliance with environmental or animal welfare standards. The survey results showed that, on average, Swiss farmers spent 3–5 % of their total working time on administrative tasks. The farmers rated the perceived burden of administrative activities as higher than the burden of overall farming activities or other office work. The data also showed that the farmers’ perceived administrative burden had increased compared to five years earlier. Finally, the results showed that 28 % of the Swiss farmers had received a penalty for non-compliance with direct payment regulations.